2016
DOI: 10.18692/1810-4800-2016-5-29-35
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of mucous membrane of maxillary sinus in its bottom perforation during dental interference

Abstract: The article is devoted to the study of pathological changes in the mucosa of the maxillary sinus in case of solution of its continuity during surgical and endodontic dental procedures. The authors performed examination and treatment of 129 patients with perforation of the maxillary sinus bottom based on the radiological and histopathological studies. The authors established that morphological changes in inflammation of the maxillary sinus mucous membrane are chronic, which explains the impossibility of autothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ment on animals have shown that a fracture of bone wall causes the development of alternative, exudative inflammation of the sinus mucous membrane, which is expressed in the formation of edema immediately after the injury, followed by its increase up to the seventh day. In the more remote periods, 4 weeks after injury, mucous membranes of the post-traumatic process with signs of metaplasia of the multi-row epithelium predominate with a stratified squamous cell and hyperfunction of the glandulas of the sinus [9][10][11].…”
mentioning
confidence: 99%
“…ment on animals have shown that a fracture of bone wall causes the development of alternative, exudative inflammation of the sinus mucous membrane, which is expressed in the formation of edema immediately after the injury, followed by its increase up to the seventh day. In the more remote periods, 4 weeks after injury, mucous membranes of the post-traumatic process with signs of metaplasia of the multi-row epithelium predominate with a stratified squamous cell and hyperfunction of the glandulas of the sinus [9][10][11].…”
mentioning
confidence: 99%